2015
DOI: 10.1007/s00394-015-1065-0
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-enriched diet induces inflammation and reduces antioxidative defense in visceral adipose tissue of young female rats

Abstract: The results suggest that fructose overconsumption-related alterations in pro-inflammatory markers and antioxidative capacity in the VAT of young female rats can be implicated in the development of adiposity, but do not affect inhibitory phosphorylation of IRS-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…(2011) showed that the impairment of placental growth and function could be due to fructose‐induced effects on placental transporters, growth factors, glucocorticoid sensitivity, and placental leptin transfer . In fact, it has been shown that fructose can induce a deranged antioxidant system by modulating glucocorticoid signaling . Moreover, the decidual cells support pregnancy by producing hormones, cytokines, and antioxidants, and it has been shown that maternal fructose consumption impairs endometrial decidualization in mice .…”
Section: Discussionmentioning
confidence: 99%
“…(2011) showed that the impairment of placental growth and function could be due to fructose‐induced effects on placental transporters, growth factors, glucocorticoid sensitivity, and placental leptin transfer . In fact, it has been shown that fructose can induce a deranged antioxidant system by modulating glucocorticoid signaling . Moreover, the decidual cells support pregnancy by producing hormones, cytokines, and antioxidants, and it has been shown that maternal fructose consumption impairs endometrial decidualization in mice .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased plasma FFAs, TG and VLDL-TG levels induce hyperlipidemia, as well as TG accumulation in extrahepatic tissues and organs. Fructose-induced lipotoxicity leads to NAFLD, lipid accumulation and autophagy in skeletal muscle [30], cardiac dysfunction [31], adipose inflammation [32], CKD [33], pancreatic islet dysfunction [34], brain oxidative stress and inflammation [35]. …”
Section: Direct Dangerous Factors Under High Fructose Consumptionmentioning
confidence: 99%
“…In different tissues of fructose-fed animals, mitochondrial dysfunction is detected, characterized by increased mitochondrial mass [62,63], decreased mitochondrial electron transport capacity [62,63], loss of mitochondrial membrane potential [64] and disturbance of antioxidant defense [32]. In turn, insulin resistance affects FFA-mediated mitochondrial uncoupling [65].…”
Section: Direct Dangerous Factors Under High Fructose Consumptionmentioning
confidence: 99%
“…In this study, we found that the level of triacylglycerol in fructosetreated, PL-stimulated HepG2 cells was significantly lower than that of cells not treated with fructose, although there was no significant difference in the absence of PL. High-fructose feeding causes alterations of lipid metabolism not only in males but also in females, particularly during pregnancy (Aijala et al, 2013;Bezerra et al, 2000;Kovacevic et al, 2015;Shortliffe et al, 2015;Thorburn et al, 1989). For example, fructose feeding during gestation was shown to induce hyperglycemia and hypertriglyceridemia in rats in early pregnancy relative to sucrose-fed rats, and also to increase hypotriglyceridemia in late pregnancy relative to normal diet-fed rats (Jen, Rochon, Zhong, & Whitcomb, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have demonstrated that increased fructose consumption is paralleled by increases in obesity, type 2 diabetes, and cardiovascular disease (Bray, Nielsen, & Popkin, 2004;Johnson et al, 2007). High-fructose diets have been shown to induce oxidative stress and insulin resistance, and result in disruption of carbohydrate and lipid metabolism in the liver and peripheral tissues of experimental animals (Bezerra et al, 2000;Huang et al, 2011;Kovacevic, Nestorov, Matic, & Elakovic, 2015;Thorburn, Storlien, Jenkins, Khouri, & Kraegen, 1989).…”
Section: Introductionmentioning
confidence: 99%